Pre-Commerce : How Companies and Customers are Transforming Business Together. - Pearson, Bob (John Wiley & Sons, 2011)
Ideas for leaders to engage directly with customers to shape their brand and marketplace successSince its debut E-commerce has been centered on the transaction, which represents less than one percent of the time we spend online. Now, we are entering the era of Pre-Commerce where customers make their own decision to buy or support a brand before the transaction. Pre-Commerce explains how the exploding use of social media channels has fundamentally changed the way customers go about making their purchasing decisions, how they educate themselves and why they choose to support certain brands abov.